2016
DOI: 10.1107/s2414314616006891
|View full text |Cite
|
Sign up to set email alerts
|

4-Chloro-1H-indole-2,3-dione

Abstract: The title compound, C8H4ClNO2, has two planar molecules in the asymmetric unit, with the non-H atoms showing a mean deviation from planarity of 0.015 and 0.022 Å, respectively. In the crystal, the molecules are linked through N—H...O hydrogen bonds to form infinite chains along [010]. They are further connected through C—H...Cl close contacts with a donor–acceptor distance of 3.682 (5) Å. No π–π interactions are observed in the structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The molecules are further linked through C6-H6Á Á ÁO2 interactions, which are also observed in the monosubstituted 7-chloroisatin (Sun & Cai, 2010). There are C-HÁ Á ÁCl interactions present in the structure of 4-chloroisatin (Juma et al, 2016), though no intermolecular halogen interactions are observed in the title compound.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…The molecules are further linked through C6-H6Á Á ÁO2 interactions, which are also observed in the monosubstituted 7-chloroisatin (Sun & Cai, 2010). There are C-HÁ Á ÁCl interactions present in the structure of 4-chloroisatin (Juma et al, 2016), though no intermolecular halogen interactions are observed in the title compound.…”
Section: Structure Descriptionmentioning
confidence: 99%